Effective software testing : a developer's guide - Aniche, Mauricio (Shelter Island, NY : Manning Publications, 2022)
Effective Software Testing teaches you a systematic approach to software testing that will ensure the quality of your code. It$1 (Bs full of techniques drawn from proven research in software engineering, and each chapter puts a new technique into practice. Follow the real-world use cases and detailed code samples, and you$1 (Bll soon be engineering tests that find bugs in edge cases and parts of code you$1 (Bd never think of testing! Along the way, you$1 (Bll develop an intuition for testing that can save years of learning by trial and error.s
1. Effective and systematic software testing -- 2. Specification-based testing -- 3. Structural testing and code coverage -- 4. Designing contracts -- 5. Property-based testing -- 6. Test doubles and mocks -- 7. Designing, for testability -- 8. Test-driven development -- 9. Writing larger tests -- 10. Test code quality -- 11. Wrapping up the book.
Includes bibliographical references and index.
Keywords: COMPUTER SOFTWARE -- TESTING